(untitled) (Journal of Enam Medical College, 2020)
Sepsis is a life-threatening condition caused by systemic host response to infection. Sepsis or septic shock is considered to be rare as initial presentation of autoimmune disease like systemic lupus erythematosus (SLE). SLE is a multisystem disorder which usually occurs in adolescent girls. So when an adolescent girl presents with septicaemia and multi-organ dysfunction, an autoimmune disease like SLE should be excluded. Here we report a 16-yearold girl initially presenting with septic shock along with multiorgan dysfunction. The patient was thoroughly evaluated and shock was managed effectively according to protocol. Later on she was diagnosed as a case of systemic lupus erythematosus (SLE). J Enam Med Col 2020; 10(1): 49-54